Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1002/mrd.1080300307
|View full text |Cite
|
Sign up to set email alerts
|

Studies on murine embryo‐derived platelet‐activating factor (EPAF)

Abstract: Studies were carried out using the splenectomized mouse bioassay (SMB) to investigate the nature of embryo-derived platelet-activating factor (EPAF) and its relationship to synthetic platelet activating factor (PAF). While both C16-PAF and embryo conditioned media (ECM) induced a significant platelet decline in the SMB at 15 min postinjection, C18-PAF induced a similar effect at 30 min postinjection. The degree of EPAF activity in ECM was not altered with increasing embryo number from 2 to 40/ml of media. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…It has been detected using several different methods including a whole-animal bioassay (O'Neill et al, 1987), in vitro bioassays (Collier et al, 1988), radioimmunoassays and mass spectroscopy (Kodama et al, 1989), and has been inde¬ pendently confirmed for the mouse (Adamson et al, 1991) and human (Punjabi et al, 1990) embryo. However, some workers (Amiel et al, 1989;Smal et al, 1990) have failed to demonstrate the release of PAF by embryos.…”
Section: Introductionmentioning
confidence: 96%
“…It has been detected using several different methods including a whole-animal bioassay (O'Neill et al, 1987), in vitro bioassays (Collier et al, 1988), radioimmunoassays and mass spectroscopy (Kodama et al, 1989), and has been inde¬ pendently confirmed for the mouse (Adamson et al, 1991) and human (Punjabi et al, 1990) embryo. However, some workers (Amiel et al, 1989;Smal et al, 1990) have failed to demonstrate the release of PAF by embryos.…”
Section: Introductionmentioning
confidence: 96%
“…Embryo-derived PAF (EPAF) may be homologous to PAF and is thought to consist of a family of PAFreceptor ligands composed predominantly of C 16 and C 18 PAF-like molecules that may be coupled to one or more regulatory molecules (reviewed by Adamson et al, 1991). EPAF is secreted by the pre-implantation embryos of several mammalian species (reviewed by O'Neill, 1991) including those of the mouse, rabbit, sheep and human.…”
mentioning
confidence: 99%
“…Nev ertheless, the standard used in bioassays was Intrauterine Signaling and Embryonic Implantation an equimolar mixture of C l 6:0 and C l 8:0 PAF. In the splenectomized mouse bioassay, both C16:0-PAF and embryo-conditioned media induced a significant platelet decline at 15 min while C18:0-PAF reacted much more slowly [111]. Also, while EDPAF activity was not significantly altered when conditioned medium was diluted 1:1,000, synthetic PAF activity was abolished at 1:10 dilution.…”
Section: Platelet-activating Factormentioning
confidence: 83%
“…Progesterone requirement is absolute. 112 Biol Signals 1996;5: [111][112][113][114][115][116][117][118][119][120][121] Estrogen may also be required, but only tran siently. The coarser (more traumatic) the in duction stimulus, the less stringent the estro gen requirement.…”
Section: Introductionmentioning
confidence: 99%